REFINING THE ENGLISH SYNTAX COURSE FOR UNDERGRADUATE ENGLISH LANGUAGE STUDENTS WITH DIGITAL TECHNOLOGIES: Received: 7th March 2023; Revised: 5th July 2023, 28th July 2023; Accepted: 2nd August 2023 - Horváthová , Božena (PUPIL: International Journal of Teaching, Education and Learning, 2023)
The English syntax course plays a crucial role in preparing future English language teachers. To enhance the teaching and learning of this subject in philological study programs, a blended approach was adopted, and a Moodle course was created. This course aimed at improving students' linguistic competence, digital skills, and time management abilities. The online course features a combination of uploaded PDF and audio lectures, scanned study materials and exercises, as well as online assignments with solutions that serve as e-portfolios, providing students with feedback on their learning progress and achievement. This study evaluates the teacher's experiences and the students’ attitudes towards the online course to determine whether incorporating digital technologies simplifies or complicates the teaching of this subject. The research methods employed are teachers' self-reflection and a questionnaire survey. In the future, further research should focus on exploring the challenges and benefits of incorporating digital technologies into linguistic education. The English syntax course plays a crucial role in preparing future English language teachers. To enhance the teaching and learning of this subject in philological study programs, a blended approach was adopted, and a Moodle course was created. This course aimed at improving students' linguistic competence, digital skills, and time management abilities. The online course features a combination of uploaded PDF and audio lectures, scanned study materials and exercises, as well as online assignments with solutions that serve as e-portfolios, providing students with feedback on their learning progress and achievement. This study evaluates the teacher's experiences and the students’ attitudes towards the online course to determine whether incorporating digital technologies simplifies or complicates the teaching of this subject. The research methods employed are teachers' self-reflection and a questionnaire survey. In the future, further research should focus on exploring the challenges and benefits of incorporating digital technologies into linguistic education.